Marketing Mix Strategy and Financial Capabilities in Improving Sharia Stock Investment - Istikomah Istikomah; Ginanjar Wira Saputra; Muhammad Yusuf (Program Studi Administrasi Bisnis, 2022)
Every year the capital market in Indonesia is increasing, stocks are the investment of choice for investors. To accommodate the needs of Muslims in Indonesia, middle class people with limited financial capabilities have begun to switch to choosing Sharia shares. This study aims to determine the Marketing Mix Strategy in the form of product, price, location and promotion and Financial Capability is the right model to improve Sharia Stock Investment Decisions. This study uses a qualitative descriptive analysis method, namely by collecting data directly from PT. Syirkah Griya Berkah by conducting observations, interviews according to the object of research. The results of this study indicate that the strategy implemented by the company has been going well from the targeted 100 investors, recorded 67 who have joined, where the four Marketing Strategy Variables and Financial Capability support each other and complement each other in improving Sharia Stock Investment Decisions. must further improve its strategy to compete with other stock competitors.